Prenatal markers of atypical neurodevelopment in children with congenital heart defects. (12th December 2022) - Carmant, Laurence S.; Boucoiran, Isabelle; Mathe, Mélodie; Boutin, Christine; Birca, Ala; Morin, Lucie
Abstract: Background: A growing body of literature demonstrates that survivors of congenital heart defects (CHD) are at increased risk of neurodevelopmental delay, which frequently manifests as motor delay during the first year of life. Objective: The aim of this study was to determine prenatal predictors of an early atypical neurodevelopment. This information could help assist decision-making during prenatal counseling. Study design: In this retrospective cohort study, we evaluated the records of 75 children with CHD followed at the Clinique d'Investigation Neuro-Cardiaque (CINC) of the CHU Ste-Justine born between 2013 and 2016. The neurodevelopmental outcome was determined using the Alberta Infant Motor Scale (AIMS) at 4 months. Associations between prenatal factors and atypical neurodevelopment (AIMS < 10th percentile) were assessed using bivariate and multivariate analyses. Results: Forty-four infants (58.7%) had atypical neurodevelopment. When there was no extra cardiac anomaly seen on prenatal ultrasound, a head to abdominal ratio (HC/AC) below 1.1 was associated with a four-fold increased risk of atypical neurodevelopment (OR = 4.54; 95% CI = 1.24–16.64 p = .023). There was no difference in identified genetic anomaly in both groups. However, there was a trend toward more extra cardiac anomalies in infants with atypical neurodevelopment (27.3%) compared to 9.7% in those with typical neurodevelopment ( p = .061). Conclusion: Our study shows that early atypical neurodevelopment affects the majority of children with CHD and highlights the importance of post-natal monitoring by a specialized team. A thorough prenatal ultrasound is important to screen for those at higher risk i.e. those with extra cardiac anomaly and HC/AC below 1.1. A larger cohort is needed to validate those results.